Train Moving Load-Induced Vertical Superimposed Stress at Ballasted Railway Tracks - Heng Wang; Ling-Ling Zeng; Xia Bian; Zhen-Shun Hong (Advances in Civil Engineering)
Ballasted railway track is an important factor that forms railway transportation over the world, which may face severe damage during operation due to the deterioration of the track ballast geometry. A practical method of evaluating train moving load-induced vertical superimposed stress in substructure by incorporating the effects of ballast characteristics and multilayered substructure is presented. The proposed method is validated by comparing with the field measurements compiled from the literature with the calculated value. It is found that the prediction accuracy of the proposed method is within ±10%, in comparison with field measurements. Meanwhile, it should be emphasized that the predicted value by traditional methods was 1.4–5.0 times field measurements. Also, key factors affecting the predicted accuracy are identified through parameter analysis by using the proposed and the traditional methods.